2017
DOI: 10.21767/2386-5180.1000159
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Helicobacter pylori Infection in Muong Children in Vietnam

Abstract: Aim: H. pylori infection is predominantly acquired in early childhood. The aim of the present study was to determine the prevalence of H. pylori infection and to identify factors associated with the infection in Muong children living in Vietnam. Materials and methods:In a cross-sectional study 918 asymptomatic individuals of all generations living together in the same home were selected from 219 households, based on cluster sampling of residential location in Hoabinh Province, Vietnam. H. pylori infection stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
13
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 35 publications
8
13
2
1
Order By: Relevance
“…These findings are consistent with several previous studies from Houston, Czech Republic, Iran and Vietnam that reported children living in a crowded household and whose parent(s) with less education are at significantly greater risks of acquiring H. pylori infection (Malaty et al, 2001;Nguyen et al, 2017;Nouraie et al, 2009;Sykora et al, 2009). Poor hygiene practices when feeding the young ones such as giving pre-chewed food and the use of same spoon by both mother and child are among the risk factors of H. pylori infection in children (Nguyen et al, 2017;Van Duynhoven & De Jonge, 2001). Our study demonstrated that testing milk bottle temperature by taking a few sucks directly and using the same cutlery to feed young children would result in a slight but significant increased risk of H. pylori infection.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with several previous studies from Houston, Czech Republic, Iran and Vietnam that reported children living in a crowded household and whose parent(s) with less education are at significantly greater risks of acquiring H. pylori infection (Malaty et al, 2001;Nguyen et al, 2017;Nouraie et al, 2009;Sykora et al, 2009). Poor hygiene practices when feeding the young ones such as giving pre-chewed food and the use of same spoon by both mother and child are among the risk factors of H. pylori infection in children (Nguyen et al, 2017;Van Duynhoven & De Jonge, 2001). Our study demonstrated that testing milk bottle temperature by taking a few sucks directly and using the same cutlery to feed young children would result in a slight but significant increased risk of H. pylori infection.…”
Section: Discussionsupporting
confidence: 92%
“…Manuscript to be reviewed are consistent with several previous studies from Houston, Czech Republic, Iran and Vietnam that reported children living in a crowded household and whose parent(s) with less education are at significantly greater risks of acquiring H. pylori infection (Malaty et al 2001;Nguyen et al 2017;Nouraie et al 2009;Sykora et al 2009).…”
Section: Discussionsupporting
confidence: 74%
“…Poor hygiene practices when feeding the young ones such as giving pre-chewed food and the use of same spoon by both mother and child are among the risk factors of H. pylori infection in children (Nguyen et al 2017;van Duynhoven & de Jonge 2001). Our study demonstrated that testing milk bottle temperature by taking a few sucks directly and using the same cutlery to feed young children would result in a slight but significant increased risk of H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been some epidemiological investigation of H. pylori infection rates in ethnic, including adults and children 4144. In 2014, Binh et al .,41 investigated H. pylori infection rates (five different methods) on 494 volunteers.…”
Section: Introductionmentioning
confidence: 99%